The Second Jungle Book - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Second Jungle Book" by Rudyard Kipling is a collection of stories published in 1895. This sequel features five tales of Mowgli navigating the laws of the jungle, from learning ancient wisdom during a drought to facing revenge, deadly treasure, and rampaging wild dogs. Three additional stories set in India explore themes of sacrifice, survival, and the natural world. Each tale is paired with poetry, creating a rich tapestry of adventure that examines the boundary between civilization and wilderness. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Second_Jungle_Book
Release date is 1999-10-01
Produced by An Anonymous Volunteer
Keywords: India -- Fiction; Jungle animals -- Fiction; Mowgli (Fictitious character) -- Fiction